Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.14302/issn.2690-6759.jpar-20-3184
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Pigeons As A Potential Hazzard For Transmission Of Some Human Protozoan Parasites

Abstract: Domestic pigeons (Columba liviadomestica) of the order Columbiformes are ubiquitous birds and can be found in virtually every town and city around the globe. Their interaction with humans and domestic animals and wild birds makes them a potential carrier of zoonotic parasites. The present study aimed to detect the prevalence of different zoonotic protozoans that affect different-aged domestic pigeons in different localities in Assiut Governorate, Egypt. A total of 50 fecal samples from 20 young and 30 adult pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
(9 reference statements)
1
4
0
Order By: Relevance
“…The investigation revealed younger pigeons exhibited a higher incidence of Cryptosporidium infection compared to their adult counterparts. This aligns with prior research conducted by [19] in Egypt, where 40% of young pigeons were found to have cryptosporidiosis, potentially attributed to their less developed immune systems. However, this observation diverges from the findings of [20], who reported no significant difference in infection rates between young pigeons (12.26%) and adults (9.57%).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The investigation revealed younger pigeons exhibited a higher incidence of Cryptosporidium infection compared to their adult counterparts. This aligns with prior research conducted by [19] in Egypt, where 40% of young pigeons were found to have cryptosporidiosis, potentially attributed to their less developed immune systems. However, this observation diverges from the findings of [20], who reported no significant difference in infection rates between young pigeons (12.26%) and adults (9.57%).…”
Section: Discussionsupporting
confidence: 90%
“…However, this observation diverges from the findings of [20], who reported no significant difference in infection rates between young pigeons (12.26%) and adults (9.57%). This discrepancy underscores the complexity of Cryptosporidium dynamics and highlights the need for further investigation into age-related susceptibility factors [19], [20].…”
Section: Discussionmentioning
confidence: 95%
“…According to research from Algeria (37), the prevalence rate of infection chicken increases significantly up to the age of 40 days before declining till the age of 64 days. Young pigeon infection rates in Egypt were 40% and adult pigeon infection rates were 20% (39).…”
Section: Infection Percentage According To Agementioning
confidence: 98%
“…Transmission of Cryptosporidium spp. occurs through inhalation or ingestion of sporulated oocysts from contaminated sources, leading to the infection cycle where sporozoites excyst in the intestine and invade the epithelial cells (4,5). This cycle can also manifest in respiratory diseases when the parasite colonizes the trachea, bronchi, air sacs, and lungs through inhalation of oocysts (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation